FC-98 Regulates TLR9-Mediated of CXCL-10 Expression in Dendritic Cells via MAPK and STAT1 Signaling Pathway. (17th February 2014) - Yang, Yonghong; Dou, Huan; Li, Xiaoqin; Song, Yuxian; Gong, Wei; Tan, Renxiang; Hou, Yayi
Abstract : Dendritic cells (DCs), as the most potent professional antigen presenting cells, play a crucial role in both innate and adaptive immune systems. Genomic bacterial DNA mimicked by unmethylated CpG motifs is discovered to possess immunostimulatory effects. CpG-DNA recognized by Toll-like receptor 9 (TLR9) on DCs arouses many immune diseases (such as cancer, viral infection, and autoimmune disorders). In this study we investigated the effects of FC-98 on CpG-induced bone marrow-derived DCs (BMDCs). The results showed that FC-98 significantly inhibited the CpG-induced BMDCs maturation and function by suppressing the expression of surface markers (CD40, CD80, CD86, and MHCII). Moreover, FC-98 downregulated the expression of C-X-C motif chemokine 10 (CXCL-10) both at the mRNA and protein level after CpG induction. Meanwhile, FC-98 markedly affected the migration of BMDCs to T cells without affecting their endocytosis capacity. Furthermore, FC-98 was confirmed to decrease CXCL-10 expression by inhibiting CpG-induced activation of MAPKs (ERK, JNK, and p38) and STAT1 signaling. Overall, these results suggested that FC-98 was a potential molecule in the treatment of CXCL-10-mediated immune diseases.